Arable Land, Climate Change and Female Employment in Agriculture in the Sahel Region - Sikwela, Misery Mpuzu; Aderemi, Timothy Ayomitunde; Mpala, Nqobile Natasha (International Journal of Energy Economics and Policy, 2026)
This study provides an empirical investigation of the nexus among arable land, climate change and female employment in agriculture within the Sahel region. The strategic importance of this study in the Sahel region lies in the fact that this sub-region of Africa is in a dire state of rainfall variability, land degradation, desertification, decline in food security, global warming and gender inequality, and thus the Sahel region is under pressure to meet the Sustainable Development Goals (SDGs 5, 13, 14 and 15) in particular within the timeline of 2030, and the African Union Agenda 2063 in general. As such, the policy implications of this study emphasize that, for the SDGs 13, 14 and 15 to be achieved within the Sahel, there is an urgent need for the policymakers in this sub-region to mitigate emission of greenhouse gas and degeneration of arable land through policies and programmes that would foster anti-grazing, sustainable agricultural practices, afforestation and sustainable extractive industries. In the same vein, since climate change induces reduction in female employment in agriculture in the Sahel, any time the policymakers in this sub-region want to achieve the SDGs 5, the policies that foster climate resilience environment should be embarked upon. Also, gender equality should be encouraged and considered when allocating arable land for agricultural purposes.